Geoneutrino oscillations approach to discriminate distributions of HPE in the earth's mantle (2018)
Neutrinos are still an intriguing matter in physics due to their odd properties, nevertheless there is a rising field on Neutrino Geoscience using their unique properties to study the Earth. This project shows the results of the simulations done in order to calculate the expected geoneutrino (electron antineutrinos from natural beta decay) signal from different mantle distributions of Heat Producing Elements and Bulk Silicate Earth models. The probability of detecting a geoneutrino is called survival probability. The average two-flavor survival probabilities and an exact approach to matter-oscillations are used. Overall, the two-flavor case shows a good fit to other studies on signal prediction from the mantle but underestimates the total flux from the Earth, while the exact-solution approach overestimates the mantle signal and gives total-flux results within the limits of the observed geoneutrino fluxes provided by KamLAND and Borexino detectors. In spite of that, further testing on the software written for the exact-solution are to be performed to evaluate the implementation accuracy. So far, geoneutrinos have proven to be an useful tool to understand the chemical composition of the planet. However, the resolution of the detectors is a significant limitation; improvements in this matter are expected in the years to come